Measurement of the Probability of a Binary Symbol «0» Erasing in a Single-Photon Asynchronous Communication Channel with a Receiver Based on a Photon Counter - A. M. Timofeev (Приборы и методы измерений)
Receiving modules of single-photon communication channels should provide the least loss of transmitted information when measuring low-power optical signals. In this regard, it is advisable to use photon counters. They are highly sensitive, but are characterized by data logging errors. Therefore, the purpose of this work was to investigate the effect of the intensity of the recorded optical radiation during the transmission of binary symbols «0» on the probability of erasing these symbols in a single-photon communication channel containing a photon counter based on an avalanche photodetector as a receiving module with a passive avalanche suppression scheme.The lower and upper threshold levels of pulses recorded at the output of the photon counter, as well as the statistical distributions of the mixture of the number of dark and signal pulses at the output of the photon counter when registering binary symbols «0» Pst0( N ) and «1» Pst1( N ) were determined. For this, a technique was used to reduce information loss. As a result, the minimum probability of erasing binary symbols «0» P(–/0) was achieved.The performed experimental results showed that to achieve the minimum probability of erasing binary symbols «0» P(–/0) = 0,11·10−2, it is important to select not only the intensity of the used optical radiation J , but also the supply voltage of the avalanche photodetector U, at which the dead time of the photon counter is −2 minimal, and its quantum detection efficiency is maximum: J0 ≥ 98,94·10−2 rel. units and U = 52,54 V.